Effect of Lumenato oral supplementation on plasma carotenoid levels and improvement of visual and experiential skin attributes. (12th January 2022) - Tarshish, Elizabeth; Hermoni, Karin; Sharoni, Yoav; Muizzuddin, Neelam
Abstract: Background: Cellular metabolism and exposure to solar irradiation result in generation of free radicals which are destructive and can lead to premature aging. Antioxidants and free radical scavengers such as carotenoids successfully protect from these free radicals by quenching and neutralizing them thereby strengthening skin barrier which leads to improved skin moisturization, desquamation, and a more youthful look. This study was designed to evaluate the consumer‐perceived efficacy of an oral supplement (Lumenato™) containing a mix of tomato carotenoids and oil‐soluble vitamins in improving skin appearance after 12 weeks of supplement use. Materials and Methods: Plasma levels of phytoene, phytofluene, zeta‐carotene, and lycopene were quantitated before and after 1‐, 2‐, 3‐, and 4‐week administration of Lumenato by 24 healthy volunteers. Part II of the study addressed skin visual attributes as assessed by validated tools (questionnaires). A total of 60 females, aged 35 to 55 years, completed part II of the study. The subjects answered questionnaires pertaining to their assessment of skin appearance before and after 12 weeks of taking the supplement. Results: There was a significant increase ( p  < 0.001) in plasma levels of phytoene, phytofluene, and zeta‐carotene after 1‐ to 4‐week treatment with Lumenato. After 12 weeks of using the supplement, the score of different skin parameters was reported to significantly improve ( p  < 0.001). Improvement was recorded in skin elasticity, firmness, brightness, skin tone, reduction in dark spots and periorbital dark circles, skin hydration, texture and fine lines and wrinkles. A significant ( p  < 0.001) improvement in overall skin condition after using the supplement was observed. The subjects noticed statistically significant ( p  < 0.001) improvement in skin elasticity, firmness, brightness, skin tone, reduction in dark spots and periorbital dark circles, skin hydration, texture and fine lines and wrinkles after 12 weeks of using the supplement. The overall skin condition also exhibited a significant improvement ( p  < 0.001). Self‐assessed improvement of the face was identified at the first time point (4 weeks) and improved significantly ( p  < 0.001) for the 12 weeks of use. Interestingly, these improvements persisted even after treatment was stopped. Conclusion: Based on the confines and conditions of this study, the use of oral supplement containing a mix of tomato carotenoids significantly increased plasma levels of phytoene, phytofluene, and zeta‐carotene, and continuous use resulted in improved facial skin attributes which were palpable by the consumers and continued even after treatment was stopped.